Determination of ion content and distribution in leaf and root in adult plants of "lluteño" maize (Zea mays L.) of the XV Región of Arica and Parinacota, Chile - Esteban,Wladimir (Universidad de Tarapacá. Facultad de Ciencias Agronómicas, 2021)
ABSTRACT The current study presents the way in which ions are distributed in an adult maize plant after flowering, and as the pressure of permanent ion stress throughout approximately six months; including all the phenological periods. The research was conducted under field conditions with the climatic characteristics of an arid or hyper-arid zone. Maize is a sensitive crop regarding the salinity of soil and water, but "lluteño" maize has a higher degree of tolerance to salinity, excess of boron (B) and other ions, this suggests that the distribution plays an important role in the tolerance mechanisms of this ecotype. The variety accumulates twice as much sodium (Na+) in the root than in the leaf, and 25 times of B more in the leaf than in the root; calcium (Ca2+), magnesium (Mg2+ and potassium (K+) were also significantly accumulated in the leaf. High concentrations of B, Ca2+, and Mg2+ were found in the thick root and K+ in the fine roots. Sodium accumulated similarly in thick and fine roots, suggesting a very active mechanism of Na+ accumulation in roots, independent of their thickness or age.